Dark tourism management and development: An exploratory analysis - Martins, Marco (2025)
A review of recent relevant literature related to dark tourism from a management perspective indicates that there is an increasing academic interest in “dark tourism consumption,” “dark tourism motivation” and “dark tourism experience.” Thus, our goal is threefold: to delve into the research development on these three constructs, to critically analyze the current research, and bring to light research gaps and interrogations that deserve further consideration. This allows for detailed present implications besides indicating possible future developments that can or will impact dark tourism management and development. Due to the multidimensional nature of the approached constructs, we conducted an exploratory study because it gives researchers the ability to synthesize multiple points of view and harness unique erspectives while still allowing us to introduce rigor and objectivity into the analysis and discussion. This chapter contributes to a deeper understanding of dark tourism management and development by providing a novel conceptual framework. Nevertheless, some constraints exist when one seeks to carry out an exploratory study because when plunging into new realities, it is only possible to formulate hypotheses. The results, however, represent a theoretical advance for dark tourism studies and provide valuable insights into how it can be better managed and developed.